Ethical Risk Management In Forex Markets: Islamic Alternatives To Conventional Derivatives - Mohammed Masood Riswi Hudawi (Penerbit Hellow Pustaka, 2025)
The globalization of financial markets has led to the emergence of a wide array of currency trading instruments designed to manage risk and enhance market efficiency. Among these are futures, forwards, options, swaps, and spot contracts, along with newer derivatives such as CFDs and spread betting. While these instruments serve important financial functions in conventional markets, their structural components often raise serious concerns within Islamic jurisprudence. The central issue lies in their frequent violation of core Shariah prohibitions, including riba (interest), gharar (excessive uncertainty), qimar (gambling), and bayʿ al-kālī bil-kālī (sale of deferred countervalues), rendering them potentially non-compliant in the context of Islamic finance. This study undertakes a detailed legal and ethical analysis of each of these instruments, drawing upon both classical jurisprudential sources and modern scholarly evaluations, including those of Mufti Taqi Usmani and regulatory bodies such as AAOIFI. Through this analysis, the paper illustrates how speculative intent, the lack of immediate possession in contracts, and the use of interest-based mechanisms compromise the permissibility of these tools. Particular attention is given to the conceptual differences between real hedging practices and speculative profit-seeking, a distinction that is often blurred in the modern FX market. The findings show a clear conflict between the operational logic of most FX instruments and the objectives of Islamic commercial law (maqāṣid al-sharīʿah). In response to these challenges, the article emphasizes the necessity for the development of Shariah-compliant alternatives that retain the economic utility of these instruments without violating ethical principles. Such solutions would ideally combine Islamic contractual structures like waʿd, ʿarbūn, and muḍārabah with rigorous Shariah supervision. By bridging the gap between modern financial practice and Islamic legal requirements, this study aims to contribute to the discourse on Islamic financial innovation and highlight the potential for ethically grounded financial instruments in the global marketplace.